(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The study aims to assess the impact of various doses of ZIP on kidney of rats. Forty five rats were assigned to three groups (15 animals/group). Control group (1) received standard diet and water, group 2 and group 3 received daily oral doses of 10 ml/kg/rat and 20 ml/kg/rat of the energy drink (ZIP) respectively for 30 days. Under light microscope no tissue changes were seen in kidney of control group. In group 2 ZIP causes vacuolar degeneration as well as coagulative necrosis of renal epithelium, vascular congestion in the glomeruli and in the interstitial part of the kidney. In group 3 ZIP leads to more atrophic glomeruli, massive necrosis of renal tubular epithelium, marked vascular dilatation and congestion in the interstitial tissue and degenerative changes of the renal tubular epithelium. It is concluded that administration of red bull to rats for 30 days will affect the histological structure of kidney and this effect is a dose dependent.